Effect of groove angle and heat treatment on the mechanical properties of high-strength steel hybrid laser-MAG welding joints. (15th January 2020) - Fulong, Zhang; Shuangyu, Liu; Fengde, Liu; Ren, Liu; Hong, Zhang
Abstract: 12-mm thick high strength steel was welded by a hybrid Laser-MAG welding. The microstructure, the micro-hardness, and the mechanical properties of the welded joints were studied by optical microscopy, scanning electron microscopy (SEM), electron backscattering diffraction (EBSD), and tensile and impact tests. The formation of the weld crack can be eliminated by a heat preservation treatment after welding. The microstructure of the weld and the heat-affected zone (HAZ) is mainly made of martensite. The highest hardness of the welded joint was measured in the HAZ and the tensile fracture is located in the center of the weld. The impact tests show that the impact fracture in the weld is brittle and the impact fracture in the HAZ is ductile. The heat preservation step added after the welding improves the impact toughness of the welded joints.